An Investigation into the Relationship Between Vision and Personality. - Godtland, Ragna (Journal of Behavioral Optometry, 2012)
Background: It is often said that the patient's personality is predictable based on the refraction or eso/exo posture, but there is little support in the literature as to the validity of this statement. This study investigated the correlation between personality and refractive error, near heterophoria, and distance heterophoria. Methods: Students and faculty (n=54) from Southern College of Optometry answered a 72-question Myers-Briggs personality survey. Participants disclosed their current refractive condition. Heterophoria was measured at distance and near using the Howell card. Results: Pearson correlations did not show significant correlation between personality and refractive error or distance/near phoria. The distance and near phoria showed a medium correlation (r=0.580) to one another. Conclusion: No significant relationship between personality and refractive error or phoria was found. There were a number of difficulties encountered that might skew this data. This study does not discount the important of behavioral observations made by each doctor throughout the examination, as personality type may be beneficial in providing the practitioner insights into how their patients relate to their visual world.